Thermo-economic analysis of transcritical CO2 cycles with bounded and unbounded reheats in low-temperature heat recovery applications. (15th August 2017) - Mirkhani, Nima; Amini, Ali; Ashjaee, Mehdi
Abstract: Performance of transcritical CO2 Rankine cycles with and without reheat process is investigated thermo-economically in low-grade waste heat recovery applications. Two reheating scenarios are proposed to evaluate the effect of bounded and unbounded reheats on the cycle. In the first method, the constant available heat flow is distributed between the evaporator and the reheater via an optimized ratio, while in the second, the required energy for the reheat process is provided with optimized additional fuel consumption. The proposed cycles are modeled and optimized for source temperatures ranging from 150 to 300 °C at fixed flow rate of 1000 kg/s. The results obtained from thermodynamic optimization indicate that reheat cycle with burning additional fuel leads to the largest power generations ranging from 14 to 57 MW depending on the source temperature, while the reheat cycle with heat stream division shows the weakest performance by producing 8–37 MW. In the thermo-economic optimization, the ratio of power output to the cycle total bare module cost has been maximized. Under these conditions, the reheat cycle with burners still shows the highest rate of power production, while economic indicators limit the power generation and introduce the simple Rankine cycle as the best option. Graphical abstract: Highlights: Performance of transcritical CO2 Rankine cycles with reheat process is investigated. Effects of bounded and unbounded reheats on the cycle performance are analyzed. Reheat cycle with additional heat is the best option in pure thermodynamic approach. Under economic limits, unbounded reheat cycle generates the highest power output. Unbounded reheat shows weaker economic performance compared to simple Rankine cycle.